Ecological Economics - Ecological Economics (Elsevier, 2026)
The journal is concerned with extending and integrating the understanding of the interfaces and interplay between "nature's household" (ecosystems) and "humanity's household" (the economy). Ecological economics is an interdisciplinary field defined by a set of concrete problems or challenges related to governing economic activity in a way that promotes human well-being, sustainability, and justice. The journal thus emphasizes critical work that draws on and integrates elements of ecological science, economics, and the analysis of values, behaviors, cultural practices, institutional structures, and societal dynamics. The journal is transdisciplinary in spirit and methodologically open, drawing on the insights offered by a variety of intellectual traditions, and appealing to a diverse readership.
FI 1.59
Q1
Keywords: Agriculture; Aquaculture & Food Science; Agriculture & Ecology; Agricultura; Ecología; Acuerdos transformativos; Transformative agreements; Ecosistemas; Economía ecológica